Fostering innovation behavior in Vietnamese commercial banks: The impact of transformational leadership, psychological empowerment, and organizational innovation climate - Sang, Tang My; Anh, Nguyen Quoc (International Journal of Innovative Research and Scientific Studies, 2025)
Innovative behavior (IB) in banks plays a crucial role in promoting sustainable development, enhancing competitiveness, and flexibly meeting the increasingly diverse needs of customers in the ever-changing financial market. This study aims to examine the impact of transformational leadership (TL) on innovative behavior through the mediating effect of organizational innovation climate (OIC). Additionally, the study investigates the moderating role of psychological empowerment (PE) in this relationship. A quantitative research method was employed, with data collected from 301 employees at 36 commercial banks in Vietnam. The findings indicate that PE, OIC, and TL directly influence IB. TL also demonstrates an impact on IB through the mediating role of OIC. Regarding moderating effects, PE significantly moderates the relationship between OIC and IB. Based on the research findings, the authors propose several policy implications to help enterprises enhance the IB of employees. Theoretically, the study provides a comprehensive overview and contributes to the theoretical foundation in the field of IB. Practically, it offers actionable recommendations for commercial banks to foster innovation and creativity within their organizations.